Calendar Anomalies in the Singapore and Chinese Stock Markets - Zhao, Jingkun (2014)
This paper examines the day of the week effect, the month of the year effect and the half-month effect on index returns from 1 January 1999 to 30 December 2013. This study selects the Singapore and Chinese stock markets as basic cases, which are stands for development countries and developing countries respectively. Combing the OLS regression and GARCH (1,1) model, we find the two stock markets are not fully efficient yet because the calendar anomalies are present in both stock markets. In terms of the day of the week effect in Singapore stock market, the Wednesday effect, Thursday effect and Friday effect are observed. Also the month of the year effect appeared, especially around the middle of the year. Moreover, the first-half month effect is prominent. Compared with Singapore, calendar anomalies in Chinese stock market are less significant, but the Wednesday effect, Thursday effect and February effect, as well as half-month effect exist. The above indicates that the efficiency of the Singapore and Chinese stock market call for improving, and investors may have opportunities to make use of the calendar anomalies to earn abnormal.